O controle judicial do orçamento da saúde no Brasil - NOLETO, Maria Clara Barros (Universidade Federal do Pará, 2017)
The right to health is a basic right established in the Brazilian Constitution and responsibility of the Public Authorities. However, the implementation of the health policies is often precarious leaving many Brazilians without access to health care. Because of this there is a growing search for the judiciary to solve eventual conflicts. The legal decisions often bring monetary impacts because of the arrest of resources implemented. This dissertation will analyze the reasons associated with this problem. The fundaments of the judges´ decisions are evaluated and it is found that they use a retributive justice perspective which brings a mismatch between the nature of the conflict and the solution given. Further investigation shows the budget as a fundamental point to the comprehension and solution of the problem, and I discuss the finality, the control and the constitutional principles related to this. In the discussion it becomes clear the importance of public expenditure and the respect to what is established in the budgetary law, reinforcing the discussion of the nature of the Brazilian Budget. I analyze the public expenditure control as well as the mechanisms available to the justice to intervene when the public administrator does not follow the law. Finally it is shown that it is possible to implicate even the head of the Executive for the measures adopted by the State which are not in agreement with the Public Budget.